Restless heart towards an existential ontology of Eros in Augustine - Centeno, Jeffrey M. (2013)
St. Augustine’s famous prayer in the Confessions, “You have made us for yourself, and our heart is restless until it rests in you,” remains today an indispensable resource of philosophical reflection. We can draw from it, particularly its understanding of eros, in our quest for meaning in our in- creasingly changing world. In a rapidly transforming world, the fundamen- tal questions of being human, like cultural solidarity, human sexuality, and integral spirituality, can take on new meanings, thus requiring contempo- rary understanding. The existential longing for self-meaning lies at the core of philosophical reflection. Meaning is necessarily reflexive; it consti- tutes the sense of being oneself within the context of manifold relations. This paper concludes with the assertion that a renewed understanding of eros in our human situation can help enhance our understanding of human sexuality and its inextricable relation to integral spirituality.
Keywords: Happiness -- Religous aspects; Self-actualization (Psychology); Human sexuality -- Religious aspects; Spiritual life